c-Maf is essential for the F4/80 expression in macrophages in vivo. - Nakamura, M; Hamada, M; Hasegawa, K; Kusakabe, M; Suzuki, H; Greaves, D; Moriguchi, T; Kudo, T; Takahashi, S (2009)
c-Maf, which is one of the large Maf transcription factors, can bind to Maf recognition element (MARE) and activates transcription of target genes. Although c-Maf is expressed in macrophages and directly regulates the expression of interleukin-10, detailed information regarding its function in the null mutant phenotype of tissue macrophages remain unknown. In this study, we demonstrated that c-Maf is specifically expressed in the F4/80 positive fetal liver and adult macrophages. The expression of F4/80, which is a tissue macrophage-specific seven trans-membrane receptor, was dramatically suppressed in the c-Maf-deficient macrophage, whereas the expression of Mac-1 was not affected, suggesting that c-Maf is not necessary for the lineage commitment of macrophages. Luciferase reporter and EMSA showed that c-Maf directly regulates the expression of F4/80 by interacting with the half-MARE site of the F4/80 promoter. These results suggest that c-Maf is required for the F4/80 expression in macrophages in vivo.